Designing Inclusive Digital Media Environments for Learners with Autism Spectrum Disorder: Integrating Artificial Intelligence and Data Analysis to Enable Adaptive Learning, Communication, and Accessibility - Faruq, Omar; Mambetaliev, Azamat; Aibek Karshiboev; Ahmed, Nisher; Khan, Rayhan; Mohammad, Nur (Journal of Posthumanism, 2025)
This paper looks at how digital tools with AI help increase learning, support interaction among learners and ensure that resources are accessible to learners on the spectrum. Because they struggle with social interaction, language and understanding senses, learners with ASD typically have a hard time in regular classrooms. It is creating digital media that makes it possible to support and include more students in the classroom. Artificial intelligence enables these environments to offer learning that adapts to what every child with ASD needs, likes and understands best. In this study the results collected by AI from trials of students using the learning platform for ASD. The visual aids and responses to emotions, students became more interested and stressed out less. The report states that when programming an AI component for a digital education system. It is important to design it with the individual visual and cognitive needs of people with ASD in mind. More research needs to focus on putting these programs into wider practice and finding out the long-term effects on students and society.